2016
DOI: 10.1212/wnl.0000000000002911
|View full text |Cite
|
Sign up to set email alerts
|

Residency Training: Work engagement during neurology training

Abstract: Objective: Work engagement, defined as a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption, can ameliorate patient care and reduce medical errors. The purpose of this cross-sectional study was to investigate work engagement among neurology residents in the region of Attica, Greece.Methods: In total, 113 residents participated in this study. Demographic and work-related characteristics, as well as emotional exhaustion and personality traits (neuroticism)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…These findings correlate with engagement findings from studies in other work environments and studies of medical residents that associated job satisfaction positively with work engagement. 10,11,31,32 Overall, employees are more engaged when they work in an environment that provides practical and psychologically meaningful support as well as advancement and promotion opportunities. 33 To be effective, support, development and advancement opportunities must be clearly communicated to FMR managers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings correlate with engagement findings from studies in other work environments and studies of medical residents that associated job satisfaction positively with work engagement. 10,11,31,32 Overall, employees are more engaged when they work in an environment that provides practical and psychologically meaningful support as well as advancement and promotion opportunities. 33 To be effective, support, development and advancement opportunities must be clearly communicated to FMR managers.…”
Section: Discussionmentioning
confidence: 99%
“…5 Work engagement is associated with positive work outcomes such as low turnover intentions, 6 reduced absenteeism, 7 increased productivity, 8 and job satisfaction in diverse groups including hospitality workers, 8,9 telecommunication workers, 6 and medical residents. 10,11 We were unable to identify any published work engagement studies involving FMR managers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in qualified doctors have shown that burnout ranges from 18 to 82% [37,38] which has a significant effect on overall mental health and work engagement [39,40]. Furthermore, burnout may lead to medical negligence and malpractice litigation, as well as suboptimal patient care practices and attitudes [38,41].…”
Section: Directions For the Futurementioning
confidence: 99%
“…is done in a different industry, namely hospitality. Other research states that the professional development of trainees allows them to support greater work autonomy to increase work engagement (Paniotis Zis, Anagnostopulos, Artemios K. Aremiadis, 2016).…”
Section: Discussionmentioning
confidence: 99%